2017
DOI: 10.1016/j.antiviral.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Global update on the susceptibility of human influenza viruses to neuraminidase inhibitors, 2015–2016

Abstract: Four World Health Organization (WHO) Collaborating Centres for Reference and Research on Influenza and one WHO Collaborating Centre for the Surveillance, Epidemiology and Control of Influenza (WHO CCs) assessed antiviral susceptibility of 14,330 influenza A and B viruses collected by WHO-recognized National Influenza Centres (NICs) between May 2015 and May 2016. Neuraminidase (NA) inhibition assay was used to determine 50% inhibitory concentration (IC50) data for NA inhibitors (NAIs) oseltamivir, zanamivir, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 34 publications
5
98
0
1
Order By: Relevance
“…For A/H3N2 and B, no virus exhibiting reduced inhibition by NAIs was detected in Japan. These results were also similar to those reported by a global surveillance, which indicated that NAI‐resistant A/H3N2 and B viruses were detected at a lower frequency (<1.0%) compared with NAI‐resistant A/H1N1pdm09 viruses . This study showed that few AA mutations in the catalytic sites of A/H3N2 viruses were found without their D151G/N mutations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For A/H3N2 and B, no virus exhibiting reduced inhibition by NAIs was detected in Japan. These results were also similar to those reported by a global surveillance, which indicated that NAI‐resistant A/H3N2 and B viruses were detected at a lower frequency (<1.0%) compared with NAI‐resistant A/H1N1pdm09 viruses . This study showed that few AA mutations in the catalytic sites of A/H3N2 viruses were found without their D151G/N mutations.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, NA AA mutations associated with NAI resistance were only H275Y of H1N1pdm09. The frequency of H275Y detected in Japan was approximately 1%, which was similar to that reported by a global surveillance . For A/H3N2 and B, no virus exhibiting reduced inhibition by NAIs was detected in Japan.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations